Explicit vocabulary teaching: developing reading confidence and achievement in disadvantaged Y6 pupils - Brownfoot, A (2020)
The aim of this study was to investigate if the teaching of vocabulary could lead to increased confidence and achievement in reading for disadvantaged Y6 children. The literature highlighted the importance of teaching vocabulary from an early age in order to have the greatest impact and to ensure that children are taught a range of strategies that they can then apply independently to work out unknown words. Following the literature review, I was interested to investigate how far daily teaching of vocabulary closes the vocabulary gap between disadvantaged and non-disadvantaged children. In addition, I also wanted to find out if explicitly teaching vocabulary impacted on children’s reading comprehension skills and confidence.